Self-reference and self-awareness - Brook, Andrew; DeVidi, Richard C. (Advances in consciousness research, 2001)
Rich in precursors (Kant and Frege) and stimulated by Castañeda's study in the logic of self-consciousness and Shoemaker's seminal paper 'Self-reference and self-awareness', the work of the past thirty-five years on self-reference and self-awareness has generated a wealth of deep, sophisticated philosophy. This volume explores the historical anticipations in Kant and Frege, brings four classic contributions together in one place, and offers five new studies. (Series A).